Factors affecting consumers' behavior towards Islamic home financing in Bank Islam (M) Berhad Kota Kinabalu, Sabah / Sitti Hajar Anisah Bacho - Bacho, Sitti Hajar Anisah
This study entitled "Factors affecting consumers' behavior towards Islamic home financing in Bank Islam (M) Berhad Kota Kinabalu, Sabah" aims to determine consumers' behavior towards IHF and identifying the influencing factors (awareness and knowledge, cost benefits, customer support and reputation) as well as the relationships between the research variables. This quantitative, descriptive research uses a survey method with an adapted questionnaire from past research (Mariatul Aida & Rosidah, 2013). A total of 150 respondents were selected from patrons of BIMB Kota Kinabalu, Sabah who were selected using convenience sampling method. Data was analyzed with SPSS 21.0 using descriptive and inferential statistical analyses. Findings showed that attitude towards IHF (mean = 3.9444) and intention to purchase IHF (mean = 3.9933) was high and overall consumer behavior (mean = 3.9640) was high. The influencing factors of awareness and knowledge (mean = 3.9520), customer support (mean = 3.8750) and reputation (mean = 3.9067) were perceived high by the respondents but cost benefits (mean = 3.5917) was perceived moderately. The relationships between awareness and knowledge (r = .593, p = .000) and cost benefits (r = .517, p = .000) are significant but moderate with consumer behavior. However, the relationships between customer support (r = .675, p = .000) and reputation (r = .774, p = .000) with consumer behavior are significant and strong. Based on the research findings, it is suggested that consumer behavior for different IHF products (BBA-Murabahah and Musharakah Mitanqisah) offered by multiple Islamic banks are investigated to get a better understanding of consumer behavior towards IHF.